أثر تطور ودائع المصرف التجاري السوري على الأرباح الصافية في الأزمة السورية - خضور حسام (Latakia University Journal - Economic and Legal Sciences Series, 2016)
إن هدف تحقيق الربح وتعظيمه هو أول ما تهتم فيه المصارف التجارية, ولكي يحقق المصرف التجاري هذه الغاية يتوجب عليه جذب وتجميع المدخرات الوطنية على شكل ودائع مصرفية, ومن ثم إعادة ضخها في الاقتصاد الوطني عبر منح التسهيلات الائتمانية والقروض الهادفة إلى تمويل الاستثمار, أو قد يقوم المصرف بالاستثمار المباشر لهذه الأموال بما يحقق له الأرباح, وإن السياسة التي يتبعها المصرف التجاري في هذا الشأن تتوقف على هيكلية الودائع وحجمها وآجالها. يتناول هذا البحث دراسة وتحليل أثر تطور الودائع في المصرف التجاري السوري على حجم الأرباح الصافية التي حققها خلال الفترة الزمنية الممتدة من عام 2000)) إلى عام ((2013, وأثر الأزمة السورية على حجم تلك الأرباح الصافية الناتجة عن تطور حجم الودائع المصرفية لدى المصرف, وذلك من خلال دراسة مسار تطورها كسلاسل زمنية بالاستعانة بما تقدمه لنا نظرية الإحصاء, حيث تم دراسة الارتباط بين أرباح المصرف التجاري السوري وبين حجم الودائع المصرفية لديه, وبناءً على ذلك تم قياس شدة واتجاه هذه العلاقة الارتباطية بين تلك المتغيرات وصولاً إلى بناء نموذج إحصائي موضوعي يعكس طبيعة واتجاه العلاقة الارتباطية بين ودائع المصرف التجاري السوري من جهة, وبين حجم الأرباح الصافية للمصرف من جهة أخرى. The goal of achieving profit and venerate is the first thing on which commercial banks are interested. And in order to achieve commercial bank this end,the bank must attract and compilation of national savings in the form of bank deposits, and then re-injected into the national economy through the granting of credit facilities and loans aimed at financing investment, or the Bank may direct the investment of these funds in order to achieve a profit, and that the policy of the Commercial Bank in this regard depends on the structure and size of deposits and maturities. This research deals with the study and analysis of the impact of the development of deposits in the Commercial Bank of Syria on the size of the net profit achieved during the time period from (2000) to (2013), and the impact of the Syrian crisis on the size of those net profits resulting from the evolution of the volume of bank deposits with the bank, through study evolution as strings of time using including lead us statistics theory, where the link has been studying the Commercial Bank of Syria earnings and the size of bank deposits has a path, and therefore has been measuring the intensity and direction of the correlation between these variables down to build a statistical model objectively reflects the nature and direction of the relationship connectivity deposits between the Commercial Bank of Syria on the one hand, and between the size of the net profits of the bank on the other hand.